2020
DOI: 10.1039/c9gc04324a
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical evolution of hydrogen peroxide on lignins

Abstract: Means of sustainable on-demand hydrogen peroxide production are sought after for numerous industrial, agricultural, and environmental applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…The results show that CD particles were photocatalytically active under simulated sunlight conditions and generated micromolar levels of H 2 O 2 (∼270 μM during 8 h of UV irradiation). Similar photocatalytic activity for H 2 O 2 synthesis under visible light has been observed in the case of TiO 2 , graphene-based nanomaterials, lignin, carbon nitride, and their related composites. …”
Section: Resultssupporting
confidence: 62%
“…The results show that CD particles were photocatalytically active under simulated sunlight conditions and generated micromolar levels of H 2 O 2 (∼270 μM during 8 h of UV irradiation). Similar photocatalytic activity for H 2 O 2 synthesis under visible light has been observed in the case of TiO 2 , graphene-based nanomaterials, lignin, carbon nitride, and their related composites. …”
Section: Resultssupporting
confidence: 62%
“…Peroxides also absorb light at ~ 200 nm 31 , a measurable amount, <1 mg L -1 was detected after four hours of irradiation. A recent study by Miglbauer et al 32 has shown that lignin itself can produce hydrogen peroxide (H 2 O 2 ) upon UV irradiation, which could indicate that lignin moieties in our system are initiating the peroxide formation upon UV irradiation.…”
Section: Lignin and Extractives In Sawdustmentioning
confidence: 75%
“…Organic dyes and lignins have been investigated as a photocatalyst of oxygen reduction to H 2 O 2 usually in the presence of a sacrificial reagent, such as oxalate and formate. [78] Shiraishi et al [79] prepared resorcinol-formaldehyde resin (25) as a reddish-orange and d) emission spectra of the dense and 23′ film and the previously reported polythiophene film. All panels are reproduced with permission.…”
Section: Light-driven Reduction Of Oxygen To H 2 O 2 On Conjugated Polymer-based Photocathodesmentioning
confidence: 98%